Screening of Nutritional Parameters for the Production of Protease from Aspergillus Oryzae - G. Srinubabu; N. Lokeswari; K. Jayaraju (E-Journal of Chemistry)
Production of protease enzyme by fungus Aspergillus oryzae was investigated. The proteolytic activity was observed when the fungus was grown in the medium containing glucose, malt extract, yeast extract, peptone, K2HPO4, MgSO4 and FeSO4. The present paper describes the screening of media components and fermentation conditions in shake flask. The organism utilized carbon sources glucose, fructose, sucrose, lactose, dextrin and starch among them glucose was found to be the best carbon source, for nitrogen sources various inorganic and organic media components were investigated among them peptone is found to be the best nitrogen source. 1% cottonseed followed by 2% Soya bean meal was found to be the best inducer. With optimized media two-fold increase in the protease production. The fungus growth depends on the concentration of carbon, nitrogen and salt solution, where as the enzyme production was also influenced by the culture time, pH and interaction between these two variables.